1996
DOI: 10.1128/jvi.70.2.1271-1276.1996
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of thymidine kinase-defective herpes simplex virus is enhanced by nucleoside

Abstract: Herpes simplex virus (HSV) mutants defective for thymidine kinase expression (TK ؊ ) have been reported to establish latent infection of sensory ganglia of mice, in that HSV latency-associated transcript is expressed, but to be defective for reactivation. In the present study, the mechanism of defective reactivation by TK ؊ HSV was investigated. Latent infection established by each of three reactivation-defective HSV type 1 mutants was studied. Reactivation in explant culture was markedly enhanced by the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Co-infection may prolong the replication of TK 2 mutant in the eye, perhaps by providing TK activity in trans, although this increase may not always be detectable. The concept of TK activity being provided in trans has been suggested previously (Coen et al, 1989b;Tenser et al, 1996), and our finding that ganglionic cells were infected dually with both TK 2 and TK + viruses addresses this possibility.…”
Section: Discussionsupporting
confidence: 73%
“…Co-infection may prolong the replication of TK 2 mutant in the eye, perhaps by providing TK activity in trans, although this increase may not always be detectable. The concept of TK activity being provided in trans has been suggested previously (Coen et al, 1989b;Tenser et al, 1996), and our finding that ganglionic cells were infected dually with both TK 2 and TK + viruses addresses this possibility.…”
Section: Discussionsupporting
confidence: 73%
“…How, then, is a tk mutant able to replicate in the nervous system of IFNR −/− mice as shown in this study? One clue comes from the observations that tk mutants can be made to reactivate by addition of thymidine to the culture medium of latently infected ganglia and that IFN-α can significantly reduce steady state levels of thymidine and thymidine metabolites in HSV-infected cells ( 58 , 59 ). Therefore, it is possible that the lack of IFN-α/β receptors in the knockout mice leads to higher intracellular levels of thymidine in the nervous system, thereby allowing a tk -deleted virus to replicate to detectable and significant levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of these enzymes in neurons are not known. Tenser et al (54) previously observed that supraphysiologial concentrations of thymidine but not uridine, dU, or dC could overcome the reactivation defects of TK Ϫ viruses. Perhaps this led to synthesis of TMP from mitochondrial TK or residual cytosolic TK that could then be phosphorylated by cellular TMPK.…”
Section: Fig 3 Plaque Autoradiography Tkmentioning
confidence: 99%